Theoretical Substantiation Of The Parameters Of The Track Softening Flat Cutting Claw (Texas Journal of Multidisciplinary Studies, 2022)
The article describes the parameters of the flat cutting claw of a comprehensive breaksmoothing track softener (flat cutting claw scanner and grinding sink angles of the blades, mounting relative to the direction of movement of the flat cutting blade blades and their opening angles, analytical expressions and the results of calculations performed on them, which allow to determine the rational values of the width of the flat-cutting jaw scan and the coverage width of the flat-cutting jaw).